Parental Smoking and Education as Determinants of Overweight in Israeli Children - Michael Huerta, MD, MPH; Haim Bibi, MD; Jacob Haviv, MD, MPH; Shimon Scharf, MD, MPH; Michael Gdalevich, MD, MPH (Centers for Disease Control and Prevention, 2006)
Introduction Obesity is a well-recognized risk factor for many chronic diseases. Pediatric overweight is an especially severe problem because its childhood onset increases the overall length of exposure to the detrimental effects of overweight, accelerates the onset of chronic disease, and affects children's physical, psychological, and social development. Several parental traits have been shown to be associated with an increased risk for childhood overweight. In our study, we quantified the mutual effects of parental education and smoking on the risk of filial overweight in a large population-based sample of Israeli schoolchildren, adjusting for the effects of age, sex, and immigration status. Methods Data were collected in 1997 and 2000 from 8623 Israeli schoolchildren aged 8 to 13 years in two cross-sectional samples. Overweight was defined as body mass index (BMI) of greater than the 85th percentile for age and sex, and severe overweight was defined as BMI greater than the 95th percentile for age and sex. Results Mean BMI was positively associated with number of parental smokers for a child. Parental smoking was an independent risk factor for both overweight and severe overweight, with a dose-response relationship between the number of parental smokers and the risk of filial overweight. Children whose parents did not attend college were at increased risk for overweight (odds ratio [OR], 1.21; 95% confidence interval [CI], 1.03-1.42) and severe overweight (OR, 1.49; 95% CI, 1.09-2.05) compared with children whose parents both attended college. Children with one college-educated parent were at increased risk for severe overweight (OR, 1.31; 95% CI, 1.004-1.71) compared with children whose parents both attended college. Conclusion Parental education and smoking are independent risk factors for filial overweight. Children of less-educated, smoking parents should be targeted for overweight prevention and intervention efforts. These findings should also be included as key messages in adult smoking prevention and cessation campaigns. Parents who smoke should be warned that not only is their own health at stake, but their children are also at increased risk for overweight and its associated diseases.